A Case in Which a Patient with Down Syndrome with an Unoperated Complete Endocardial Defect Who Developed a Brain Abscess after Multiple Tooth Extractions was Treated Immediately through Multidisciplinary Collaboration Prepared in Advance - YOSHINAKA, Taiga; MIYAZAKI, Hironori; ODA, Aya; OGATA, Katsuya; TAKAHASHI, Tamayo; MUKAI, Akari; FURUTANI, Chiaki; ODA, Yuki; YOSHIDA, Yuriko; OKADA, Yoshiyuki; OUE, Kana (Journal of the Japanese Society for Disability and Oral Health, 2024)
Introduction：Congenital heart disease is observed in approximately half of patients with Down syndrome. During the bleeding procedures, administration of antibiotics to high-risk patients is recommended to prevent infective endocarditis （IE）. We experienced a case of a Down syndrome patient with complete atrioventricular deficiency for which surgery had not been performed and who developed a brain abscess after teeth extraction.Case：The patient was a 28-year-5-month-old female with the chief complaint of teeth extraction. Past medical history：Endocardial defect （no surgery performed）. History of current illness：A facility staff noticed her loose teeth and visited our department. Current symptoms：height 141cm, weight 47kg, SpO2 83％（O2 2l/min）. Seven teeth needed to be extracted.Treatment and Course：At the first visit, body movement to refuse oral examination was observed, and it was predicted that treatment under physical restraint would have a high risk of hypoxia. Since the risk of IE increases with multiple tooth extractions, a single treatment under general anesthesia was proposed. However, there was a risk that cardiac function would irreversibly decline due to changes in hemodynamics associated with general anesthesia. According to the consultation results, it was decided to treat the patient with multiple outpatient treatments through cooperation between multiple facilities, and arrangements were made so that the patient could be hospitalized immediately in case of onset of IE. After the third tooth extraction, the patient developed a fever and was immediately hospitalized as planned in advance. After careful examination, a brain abscess was found, so ampicillin sodium was administered, and the patient was discharged 13 weeks later.Discussion and Conclusion：In this case, we were able to respond immediately to a brain abscess in a Down syndrome patient with untreated congenital heart disease by predicting the onset of IE and coordinating the cooperation between multiple facilities. For patients in IE high-risk groups, it is important to keep in mind the onset of IE and take prompt action through multidisciplinary collaboration.